Genetic Risk Factors for Idiopathic Urolithiasis: The Causative Role of Genes in Stones Formation - Jatmiko susilo (Universitas Ngudi Waluyo, 2021)
Background: The genetic factor of urolithiasis plays an important role in the etiology. Elucidation of responsible genes can lead to better targeted gene therapy and prevention in the future. This article aims to explain various genetic factors that play a role in kidney stone formationÂ Method: A review article on urolithiasis based on a genetic approach is reported to underlie stone formation. A total of 41 abstracts and research articles published by internationally reputed journals were selected based on the keywords genetic factors and urolithiasis.Â Summary: A deeper understanding of the genetic factors that play a role in the mechanisms of stone formation and advances in molecular and pharmacogenomics have revolutionized diagnosis and treatment, and paved the way for the identification of new therapeutic targets and treatment approaches based on genetic engineering.